1987
DOI: 10.1161/01.cir.76.1.163
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inotropic stimulation on normal and ischemic myocardium after coronary occlusion.

Abstract: During acute myocardial ischemia, there exists a zone of myocardial dysfunction that surrounds the central ischemic area that has been termed the functional border zone. We hypothesized that this nonischemic but dysfunctional myocardium may respond to an inotropic challenge. To . We conclude that (1) nonischemic myocardium adjacent to ischemic tissue responds to inotropic challenge, (2) dobutamine produces a significant decrease in the size of the functional border zone, and (3) dynamic changes in wall thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 29 publications
1
10
1
Order By: Relevance
“…Buda et al 5 also found little response to dobutamine in the center of an acutely ischemic region. However, Vatner and coworkers 6 -8 reported that ^-adrenergic stimulation of ischemic myocardium with isoproterenol resulted in increased paradoxical bulging and S-T segment elevation in conscious dogs with acute ischemia.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Buda et al 5 also found little response to dobutamine in the center of an acutely ischemic region. However, Vatner and coworkers 6 -8 reported that ^-adrenergic stimulation of ischemic myocardium with isoproterenol resulted in increased paradoxical bulging and S-T segment elevation in conscious dogs with acute ischemia.…”
mentioning
confidence: 95%
“…Intravenous administration of inotropic agents, however, complicates the assessment of the eflFect on ischemic myocardium because of simultaneous stimulation of nonischemic adjacent and distant regions with subsequent changes in ventricular hemodynamics. 5 This study was undertaken for evaluation of the effects of inotropic stimulation on the ischemic myocardium, its regional blood flow, and blood flow distribution under similar global hemodynamic conditions by regional infusion of dobutamine into the ischemic myocardium. Specifically, we tested whether regional myocardial blood flow and function are matched during steady-state ischemia under conditions of regional inotropic stimulation or whether dobutamine induces a state of "relative" ischemia characterized by an imbalance between decreased flow and increased function.…”
mentioning
confidence: 99%
“…Functional imaging with stress echocardiography (5,6) and stress magnetic resonance imaging (MRI) (7)(8)(9)(10) identifies myocardial ischemic dysfunction in regions of supply-demand mismatch. Since both the perfusion and the functional approaches are intended to quantify the myocardium at risk, the presence of a functional border zone (11)(12)(13)(14)(15)(16)(17) consisting of dysfunctional but normally perfused myocardium adjacent to ischemic tissue may cause differences in relative size of the ischemic area depicted by the two techniques. If myocardial ischemia assessment is based on regional impairment of function, the presence of a functional border zone would cause overestimation of the myocardium at risk.…”
mentioning
confidence: 99%
“…A number of experimental studies have demonstrated a functional border zone that extends 4-5° (11)(12)(13)16) into normally perfused myocardium on either side of the perfusion defect caused by coronary arterial occlusions. However, whether a functional border zone develops adjacent to hypoperfused myocardium caused by non-occlusive coronary artery stenosis is not clear.…”
mentioning
confidence: 99%
See 1 more Smart Citation